2013
DOI: 10.1242/dev.090878
|View full text |Cite
|
Sign up to set email alerts
|

A global pattern of mechanical stress polarizes cell divisions and cell shape in the growing Drosophila wing disc

Abstract: Organismal development is under genetic control. Ultimately, mechanical forces shape embryos. If we want to understand the precise regulation of size and shape in animals, we must dissect how forces are distributed in developing tissues, and how they drive cell behavior to shape organs. This has not been addressed fully in the context of growing tissues. As cells grow and divide, they exert a pressure on their neighbors. How these local stresses add up or dissipate as the tissue grows is an unanswered question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
230
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(254 citation statements)
references
References 57 publications
23
230
0
1
Order By: Relevance
“…In keeping with this idea, Campinho et al found that there is a reduction in tension following oriented cell division in the zebrafish embryo, which assists in tissue spreading during gastrulation [15]. A similar dissipation of stress by oriented cell division was also observed in the developing Drosophila wing disc [25]. In the wing disc it appears that the anisotropic tension is itself caused by differential cell proliferation across the disc [23].…”
Section: Why Might It Be Useful For Cells To Orient According To Mechmentioning
confidence: 84%
See 1 more Smart Citation
“…In keeping with this idea, Campinho et al found that there is a reduction in tension following oriented cell division in the zebrafish embryo, which assists in tissue spreading during gastrulation [15]. A similar dissipation of stress by oriented cell division was also observed in the developing Drosophila wing disc [25]. In the wing disc it appears that the anisotropic tension is itself caused by differential cell proliferation across the disc [23].…”
Section: Why Might It Be Useful For Cells To Orient According To Mechmentioning
confidence: 84%
“…Indeed, computational modelling suggests that the anisotropic distribution of tension could actually be generated by differential proliferation across the disc, with high levels of proliferation in the distal regions inducing the circumferential tension on proximal cells [23]. Laser ablation experiments confirmed the existence of these force anisotropies across the disc by demonstrating that tension at proximal/distal cell junctions increases towards the periphery of the wing disc [25]. So, how do these patterns of forces correlate with the orientation of divisions?…”
Section: Does Mechanical Force Orient Cell Division In Tissues?mentioning
confidence: 99%
“…21, using a point scanning confocal microscope Leica SP8 with a 363 objective (numerical aperture 1.4), 36 h ACI (WT in tub-dmyc). Discs showing rapid drop-down of cell division were excluded from the analysis.…”
Section: Letter Researchmentioning
confidence: 99%
“…Removal of the signal from the peripodal cells and selection of the signal from the junction plane were performed by using a home-made Matlab macro for selective plane projection (inspired by ref. 21). For every x-y pixel, the z-plane with the maximal E-cad::GFP intensity (calculated by summing pixel intensity on a 50 pixel 3 50 pixel square at every plane) was kept and used to retrieve RFP signal in the same plane.…”
Section: Letter Researchmentioning
confidence: 99%
“…More specifically, the fast-growing population should experience compression, while the slow-growing population should be stretched in the tangential direction of the fast-growing clone [10,55] (Figure 2A). Accordingly, a slight increase in growth rate in the center of the wing imaginal disc leads to the compression of the medial cells and stretching of the more-lateral cells [56,57]. Stretching of loser cells by faster-proliferating winner cells was proposed to be responsible for loser cell elimination [10,55] …”
Section: Competition For Space and Mechanically Induced Deathmentioning
confidence: 99%